Myocardial perfusion at rest in uncomplicated type 2 diabetes patients without coronary artery disease evaluated by 320-multidetector computed tomography: A pilot study. Issue 5 (February 2018) - Cai, Xiangyi; Zhang, Shuihua; Deng, Dabiao; Li, Honglin; Guan, Xueqing; Fang, Jin; Zhou, Quan
Abstract : Abstract: Using computed tomography myocardial perfusion imaging (CTP) to investigate resting myocardial perfusion alterations in uncomplicated type 2 diabetes mellitus (T2DM) patients without obstructive coronary artery disease (CAD). A total of 34 participants with 544 myocardial segments were included prospectively: 17 uncomplicated T2DM patients with no significant coronary artery stenosis on coronary computed tomography angiography and 17 healthy controls. Myocardial perfusion was evaluated by transmural perfusion ratio (TPR). Parameters of cardiac structure and function were measured for cardiac comprehensive assessment. Analyses included descriptive statistics and group comparisons. TPR of segments 5, 7, 9, 10 to 14 were significantly reduced in T2DM group compared with controls ( P  < .05). When 16 myocardial segments were localized into different areas according to the wall orientations, axial levels of left ventricle and coronary artery territories, respectively, TPR of each area in T2DM group were significantly lower than those in the control group ( P  < .05). No significant differences were found in cardiac anatomy and function analyses between 2 groups. In uncomplicated T2DM patients without obstructive CAD, myocardial perfusion impairments were present and may develop prior to cardiac morphological and functional abnormalities, which can be early detected by CTP.